2000
DOI: 10.1021/jo000245u
|View full text |Cite
|
Sign up to set email alerts
|

Stereoelectronic Effect on One-Electron Reductive Release of 5-Fluorouracil from 5-Fluoro-1-(2‘-oxocycloalkyl)uracils as a New Class of Radiation-Activated Antitumor Prodrugs

Abstract: A series of 5-fluoro-1-(2'-oxocycloalkyl)uracils (3-11) that are potentially novel radiation-activated prodrugs for the radiotherapy of hypoxic tumor cells have been synthesized to evaluate a relationship between the molecular structure and the reactivity of one-electron reductive release of antitumor 5-fluorouracil (1) in anoxic aqueous solution. All the compounds 3-11 bearing the 2'-oxo group were one-electron reduced by hydrated electrons (eaq-) and thereby underwent C(1')-N(1) bond dissociation to release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…14,15 Recently, we reported that 5-fluorouracil (5-FU) and 5-fluorodeoxyuridine (5-FdUrd) derivatives possessing 2-oxoalkyl groups are radiation-activated prodrugs releasing representative antitumor agents 5-FU and 5-FdUrd, respectively, to cause effective cytotoxicity against hypoxic tumor cells. [16][17][18][19][20] Mechanistic studies showed that these prodrugs undergo reduction by capturing reducing hydrated electrons ðe À aq Þ generated by radiolysis of water. 21 This family of prodrugs are radiation-activated only in the hypoxic tumor cells, but not in the aerobic normal cells with sufficient oxygen concentration for trapping e À aq .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Recently, we reported that 5-fluorouracil (5-FU) and 5-fluorodeoxyuridine (5-FdUrd) derivatives possessing 2-oxoalkyl groups are radiation-activated prodrugs releasing representative antitumor agents 5-FU and 5-FdUrd, respectively, to cause effective cytotoxicity against hypoxic tumor cells. [16][17][18][19][20] Mechanistic studies showed that these prodrugs undergo reduction by capturing reducing hydrated electrons ðe À aq Þ generated by radiolysis of water. 21 This family of prodrugs are radiation-activated only in the hypoxic tumor cells, but not in the aerobic normal cells with sufficient oxygen concentration for trapping e À aq .…”
mentioning
confidence: 99%
“…29 It is therefore evident that IQ-FdUrd is activated to release 5-FdUrd via reduction by e À aq occurring exclusively under hypoxic conditions, similar to the 5-FdUrd prodrugs possessing 2-oxoalkyl groups. [16][17][18][19][20] We also conducted laser flash photolysis studies on the reductive activation of IQ-FdUrd employing dimethylaniline (DMA) as an electron donor to get further mechanistic insight into the reductive release of 5-FdUrd. 30 Figure 3a shows the transient absorption spectra created in the 266 nm laser flash photolysis of IQ-FdUrd and DMA in phosphate buffer (pH 7.4).…”
mentioning
confidence: 99%
“…Recently, the concept of mutual prodrugs in which two different antineoplastic agents are coupled directly or by means of a spacer has become well accepted [8][9][10][11][12][13][14][15][16][17]. This technique can be used to overcome many problems including poor solubility or absorption, patient acceptability, drug instability and toxicity, and especially drug resistance [11].…”
Section: -Fluorouracil (5-fumentioning
confidence: 99%
“…Stock solution (10 µM) of samples was prepared in dimethylsulfoxide (DMSO) and diluted with various concentrations with serum-free culture medium. The in vitro antitumor activity of compounds 1-6 and 5-Fu were determined by MTT assay method [10]. Briefly, exponentially growing B16 or CHO cells were seeded in 96-well plates (5000 to each well) and allowed to attach overnight.…”
Section: In Vitro Antitumor Activity Experimentsmentioning
confidence: 99%
“…To tackle these problems, numerous modifications of the 5-FU structure have also been performed. The N-1 or/and N-3 substituted derivatives, in particular, have exhibited improved pharmacological and pharmacokinetic properties, including increased bioactivity, selectivity, metabolic stability, absorption and lower toxicity [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%